The impact of sectoral macroprudential capital requirements on mortgage loan pricing: Evidence from the Belgian risk weight add-on - Stijn Ferrari; Mara Pirovano; Pablo Rovira Kaltwasser (National Bank of Belgium, 2016)
In December 2013 the National Bank of Belgium introduced a sectoral capital requirement aimed at strengthening the resilience of Belgian banks against adverse developments in the real estate market. This paper assesses the impact of this macroprudential measure on mortgage lending spreads. Our results indicate that affected banks reacted heterogeneously to the introduction of the measure. Specifically, mortgage-specialised and capital-constrained banks increase mortgage lending spreads by a greater amount. As expected, the impact of the measure on mortgage loan pricing has been rather modest in economic terms.
Keywords: E44; E58; G21; G28; 330; Systemic risk; macroprudential policy; bank capital requirements; real estate; Kapitalbedarf; Systemrisiko; Hypothek; Belgien